Pengaruh Solution Heat Treatment terhadap Sifat Fisis dan Mekanik Proses Pengelasan Fssw AA6063-T5 - Ciptadi Natawiguna; Nurul Muhayat; Teguh Triyono (Mekanika: Majalah Ilmiah Mekanika, 2018)
Friction stir spot welding (FSSW) of aluminum alloy AA6063-T5 will decrease the strength and hardness. Physical and mechanical properties of aluminum alloy can be improved by heat treatment. Heat treatment is affected by temperature and holding time. The heat treatment process used for this research was solution heat treatment with temperature variation 470, 500, 530 oC and holding time 1 and 2 hours. The tests included microstructure test, tensile shear test and vickers hardness test. Result of the research, it was found that Mg2Si particles were precipitated from the grain boundaries part into the aluminum matrix with the coarser size and the distance was increasing as the temperature and the holding time increases. The highest shear tensile strength of 3735,2 N was obtained from the temperature variation of 470 oC and the holding time of 1 hour. The lowest tensile shear strength of 3172,6 N was obtained from temperature variation of 530 oC and 2 hours of holding time. The highest hardness value was obtained of 470 oC variation and 1 hour was 43,7 HVN and the lowest hardness value at 530 oC variation and 2 hours of holding time was 30,1 HVN.